The Influence Of Perceived Brand Authenticity And Self-Brand Congruence On Consumer Satisfaction (Survey Of Iphone Smartphone Users At The University Of Perjuangan) - Zannath, Reza Faisal; Fitriadi, Budhi Wahyu; Yusnita, Rita Tri (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the influence analysis of perceived brand authenticity and self-brand congruence on consumer satisfaction (a survey of iPhone smartphone users at Perjuangan University). The method used in this study is causality through a survey approach. With a research sample of 100 iPhone Smartphone Users at the University of Perjuangan. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Perceived Brand Authenticity obtained from Perceived Brand Authenticity on iPhone Smartphone Users at Perjuangan University had good criteria. Self-Brand Congruence at Iphone has good criteria, Consumer Satisfaction with iPhone Smartphone Users at Perjuangan University has good criteria. Taken together Perceived Brand Authenticity and Self-Brand Congruence have a significant influence on Consumer Satisfaction Partially Perceived Brand Authenticity has a significant influence on Consumer Satisfaction Partially Self-Brand Congruence has a significant effect on Consumer Satisfaction